Countermapping interventions (re-)telling river-town map stories - Amorsolo, Dominique Sasha N. (Banwaan: The Philippine Journal of Folklore, 2022)
Access online through this link: https://journals.upd.edu.ph/index.php/Banwaan/article/view/8833/7857